Severe systemic cutaneous adverse reactions following camrelizumab therapy: a case report and literature review - Sun, Yuan-dong; Guo, Wen-jia; Han, Jian-jun (Frontiers in Immunology, 2025)
We report a case of a 42-year-old female patient with lip squamous cell carcinoma who developed a severe systemic cutaneous adverse reaction following camrelizumab therapy. The patient had previously undergone wide local excision, chemotherapy, and radiotherapy before receiving camrelizumab in combination with transcatheter arterial chemoembolization. Ten days after the initial infusion, she presented with generalized desquamation, hyperpigmented lesions, and skin breakdown involving the trunk and extremities, most prominently on the hands, arms, and legs. Corticosteroid therapy led to a rapid reduction in pruritus and gradual improvement of cutaneous lesions, with marked healing observed after one week. Remarkably, upon rechallenge with camrelizumab, only mild residual hyperpigmentation was noted without recurrence of severe symptoms. This case highlights the importance of recognizing camrelizumab-associated dermatologic toxicity, emphasizes the role of timely corticosteroid intervention, and suggests that cautious rechallenge may be feasible in selected patients. Further investigation is warranted to elucidate the immunopathological mechanisms underlying severe skin reactions to PD-1 inhibitors and to optimize prevention and management strategies.